Wacky and Wonderful Misconceptions About Our Universe - Kirby, Geoffrey (Astronomers' Universe,, 2018)
From unicorns on the Moon to UFOs piloted by Martian bees, this book chronicles some of the strangest ideas that have been put forward - and have actually been believed in -- about our Solar System. Drawn from tales dating from the Middle Ages to the present, this collection of stories takes readers on an imaginative and wild ride through the ages and minds of some of the wackiest, tackiest, most outlandish concepts in astronomy, cosmology and physics. Follow along as Geoff Kirby recounts each quirky idea in detail and explains how these theories fare against modern astronomical research and technologies.